Diagnóstico de la calidad de energía del suministro eléctrico de los grupos electrógenos de la estación Quijos del poliducto Shushufindi - Quito de la EP Petroecuador durante el año 2015. Implementación de un sistema automatizado mediante transferencia tecnológica para mejorar la eficiencia eléctrica. - Chuquimarca Salazar, Manuel Alfredo (2016)
The backup power of the Quijos Station is very important because of the continuous network failures of the Electric Company; it is not possible to transport by-products from oil stops. Into the principal difficulties of the old system, it is outlined the excitation current regulation, which makes difficult the stress adjustment on the terminals in the generator, and the lack of precision in the frequency regulation. It has been proposed to implement an automated system genset through DSE 7320 technology, allowing the increase of the efficiency and the stability of the energy provided by the electricity generation system of the previously mentioned station, because it is related to the professional and industrial part in this field. Firstly, the design and the construction of the control panel were made in the Osayacu Station workshops, to finally conclude with the proposal, raised in the Quijos Station. Regarding to the voltage regulation, the AVR used is the SS053 card. It is necessary to clarify that some relevant calculation were done for the voltage regulations, which indicates how much voltage change is expected in the terminals, between the vacuum condition, and in full load. When the load will be assigned, it will not be under the standardized levels as energy quality, resulting an approximately 2 volts of difference. The frequency regulation was achieved due to the calibration of the injection pump in the internal combustion engine, with a digital display in the DSE 7320 modules. Finally, new measurements were performed with the Shark 200 meter, under the CONELEC normative, to carry out the stability comparative analysis of the electric system before and after its implementation, obtaining as result, a higher stability in the new generation system, with an approximated voltage of 480 VCA, a 60,3 Hz of frequency, near of 99,50 % as an increase of availability, and 30 seconds as the answer time.